Dickens, Grip and the Corvid Family - Michael Hollington (Caliban: French Journal of English Studies)
Dickens loved animals, birds and flowers, and kept many pets: dogs, cats, and at one period of his life, ravens. This article is concerned with these latter, in the context of the crow family (Corvidae) to which they belong. I examine here the biographical evidence of his relationship to ravens, as well as his representation of the entire family of Corvidae in his fiction, starting of course with Grip in Barnaby Rudge. This most famous of Dickens’s ravens is associated with the devil. Elsewhere in Dickens other members of the crow family are seen as evil, such as the crow itself, the totem of Grandfather Smallweed in Bleak House. But rooks, in David Copperfield and elsewhere, are seen by contrast as peaceable, harmless creatures, so as to complicate the picture of corvids in Dickens as a whole.